Sustainable management of globally significant endemic ruminant livestock in West Africa: Estimate of livestock demographic parameters in Senegal - Ejlertsen, M.; Poole, Elizabeth J.; Marshall, Karen (International Livestock Research Institute, 2012)
This report describes the results of a 12-month retrospective survey for estimating livestock demographic parameters of endemic ruminant livestock (ERL) kept by smallholders in selected sites in Senegal. The demographic parameters estimated included natural rates, such as parturition, abortion and mortality rates, as well as management rates, such as offtake and intake rates.